Core level photoelectron spectroscopy probed heterogeneous xenon/neon clusters. (June 2017) - Pokapanich, Wandared; Björneholm, Olle; Öhrwall, Gunnar; Tchaplyguine, Maxim
Abstract: Binary rare gas clusters; xenon and neon which have a significant contrariety between sizes, produced by a co-expansion set up and have been studied using synchrotron radiation based x-ray photoelectron spectroscopy. Concentration ratios of the heterogeneous clusters; 1%, 3%, 5% and 10% were controlled. The core level spectra were used to determine structure of the mixed cluster and analyzed by considering screening mechanisms. Furthermore, electron binding energy shift calculations demonstrated cluster aggregation models which may occur in such process. The results showed that in the case of low mixing ratios of 3% and 5% of xenon in neon, the geometric structures exhibit xenon in the center and xenon/neon interfaced in the outer shells. However, neon cluster vanished when the concentration of xenon was increased to 10%. Highlights: Co-expansion setup is suitable for producing binary Xe/Ne clusters. Appropriate temperature, pressure, and mixing ratios should be strictly controlled. Low mixing ratio, Xe formed in the core and Xe/Ne interfacing in the outer shell. High mixing ratio, only pure Xe clusters were detected.